Cognitive Computing - ICCC 2020 : 4th International Conference, held as part of the Services Conference Federation, SCF 2020, Honolulu, HI, USA, September 18-20, 2020 : proceedings /: 4th International Conference, held as part of the Services Conference Federation, SCF 2020, Honolulu, HI, USA, September 18-20, 2020 : proceedings. ([2020]) - Unknown
No abstract available